2020
DOI: 10.3390/plants9010077
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Influence of Apple Peel Polyphenol Extract Fortification on the Characteristics of Probiotic Yoghurt

Abstract: The aim of the current study was to evaluate the effect of apple peel polyphenol extract (APPE) on the physicochemical and microbiological properties of probiotic yoghurt. Five concentrations of APPE were added in probiotic yoghurt as: (1) CTL, control without APPE; (2) AE1, addition of 1% APPE; (3) AE2, addition of 2% APPE; (4) AE3, addition of 3% APPE; (5) AE4, addition of 4% APPE; and (6) AE5, addition of 5% APPE. The prepared probiotic yoghurt was stored at 4 °C for 21 days and analyzed for physicochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 38 publications
7
25
0
Order By: Relevance
“…In line with Ahmad et al. (2020) results, it was observed that the addition of AP in yogurt reduced the syneresis while increased firmness and viscosity. A similar phenomenon was observed in yogurt with addition of apple pomace (Wang et al., 2020).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…In line with Ahmad et al. (2020) results, it was observed that the addition of AP in yogurt reduced the syneresis while increased firmness and viscosity. A similar phenomenon was observed in yogurt with addition of apple pomace (Wang et al., 2020).…”
Section: Resultssupporting
confidence: 87%
“…The same trend was demonstrated by Ahmad et al. (2020) where the AP polyphenol extract moderately reduced the pH of yogurt comparatively to control. Similarly, according to Demirbüker Kavak et al.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations